Psychosocial factors in pregnancy and birthweight: Path analysis. Issue 7 (20th April 2016) - Dolatian, Mahrokh; Mahmoodi, Zohreh; Alavi‐Majd, Hamid; Moafi, Farnoosh; Ghorbani, Maryam; Mirabzadeh, Arash
Abstract: Aim: Birthweight is known to be affected by several factors. In the present study a relationship model of psychological and economic determinants of birthweight was designed and tested. Methods: This prospective study involved 400 pregnant women in four districts of Tehran, Iran. The subjects were selected through a multistage sampling method. Seven questionnaires (socioeconomic status; Holmes and Rahe Stress Scale; Perceived Stress Scale; 21‐item Depression, Anxiety, and Stress Scale [DASS‐21]; perceived social support; pregnancy‐related anxiety scale; and domestic violence questionnaire) were used to assess participant psychosocial and economic conditions. In order to collect post‐partum information about the mother and the infant, the women were followed up until delivery. Data were analyzed using SPSS‐16 and Lisrel‐8.8. Results: Based on the obtained path diagram, the greatest adverse effects on birthweight were exerted directly by DASS‐21 score (B = −0.14) and indirectly by stressful life events (B = −0.037). Among variables that affected birthweight in both paths, socioeconomic status and perceived stress had the strongest overall effects on birthweight (B = 0.203 and −0.1024, respectively). Conclusion: According to the path analysis model, psychosocial and economic factors can directly/indirectly affect birthweight.